Characterization of environmentally friendly degradation of hexabromocyclododecane by a Bacillus strain HBCD-sjtu. (November 2019) - Shah, Syed Bilal; Huang, Ling; Hu, Haiyang; Wang, Weiwei; Ali, Fawad; Xu, Ping; Tang, Hongzhi
Abstract: HBCD (1, 2, 5, 6, 9, 10-hexabromocyclododecane) is an environmental pollutant widely distributed across the globe. Toxicological studies have shown that HBCD may cause cancer and affect human thyroid hormones; however, little research has been performed on HBCD degradation. In this study, we isolated and identified a species of Bacillus strain named HBCD-sjtu using a degradation process, where HBCD was the sole carbon source. We used morphological, biochemical, and phylogenetic analyses to categorize the isolate as a Bacillus strain. Conditions for the growth of Bacillus sp. HBCD-sjtu were optimized at 30 °C, pH 7, and 200 rev/min with 1.5 mM maximum HBCD-tolerating ability. Four different intermediates, 1, 5, 9-cyclododecatriene (CDT), 1, 5-cyclododecadiene (CDD), cyclododecene, and 3, 9-dodecadiene were identified based on gas chromatography-mass spectrometry analyses. Our results provide novel insight into the bacterial degradation of HBCD, and lay the groundwork for additional research into environmentally friendly applications of HBCD biodegradation.